Clinical efficacy of Danshen preparation in the treatment of vascular cognitive impairment: A systematic review and meta-analysis - Li, Yunze; Yao, Yangjing; Cao, Xinran; Yi, Nan; Chen, Anqi; Li, Jianjun; Wu, Minghua (Frontiers in Aging Neuroscience, 2023)
We included a total of 12 RCTs that included data on clinical therapeutic effects. The evaluation criteria included the following: National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), Barthel Index (BI), Mini-Mental State Assessment (MMSE), Montreal Cognitive Assessment (MOCA), Activities of Daily Living Scale (ADL), treatment effect index, and incidence of adverse reaction index. In the included studies, the observation groups included 656 cases and the control groups included 660 cases. The results of the MA were as follows: the mean difference (MD) value after combining the effect size for NIHSS was -2.91, with a 95% confidence interval (CI) of -4.22 to -1.59; the combined effect quantity hypothesis test revealed that Z=4.33 (P<0.00001), indicating that the score pertaining to the degree of neurological deficit (NIHSS) in the observation group after treatment was significantly lower than that in the control group. This result reveals that treatment with a Danshen preparation can reduce neurological deficit in VCI patients. The MD value after combining the effect size for mRS was -0.73, with a 95% CI of -0.85 to -0.61; the result of the combined effect quantity hypothesis test revealed that Z=12.29 (P<0.00001). These results indicate that the degree of disability was significantly reduced after treatment in the observation group. The MD value after combining the effect size for MMSE was 2.09, with a 95% CI of 0.33 to 3.84; the result of the combined effect quantity hypothesis test showed that Z=2.33 (P=0.02). These results indicate that the cognitive function score (MMSE) of the observation group after treatment was significantly higher than that of the control group and suggests that the cognitive function of VCI patients was improved after treatment with Danshen preparations. The MD value after combining the effect size for ADL was 8.79, with a 95% CI of 3.52 to 14.06; the result of the combined effect quantity hypothesis test indicated that Z=3.27 (P=0.001).